A dual‐process model of how incorporating audio‐visual sensory cues in video advertising promotes active attention. Issue 8 (23rd April 2020) - Simmonds, Lucy; Bogomolova, Svetlana; Kennedy, Rachel; Nenycz‐Thiel, Magda; Bellman, Steven
Abstract: Capturing consumers' attention to video advertising is a key marketing challenge. Using real video advertising viewed by a sample of consumers matching the US population on age and gender, the authors examined attention to audio‐visual and visual sensory cues identifying the brand using a biometric measure, phasic heart rate. The findings show differences in attention type depending on which senses are stimulated by the sensory cue. This research uncovers a mechanism (internal processing) for how consumers process multisensory cues (audio‐visual) in video advertising and confirms visual sensory cues can elicit automatic attention through the orienting response. In addition to the dual‐coding explanation for the superiority of audio‐visual sensory cues, the present research suggests a second reason: that audio‐visual sensory cues can elicit additional internal processing of the brand name, resulting in active attention and better storage of the brand in memory. This has implications for the limited capacity model of motivated mediated message processing, as well as for marketers relating to the type of content recommended to follow an audio‐visual or visual sensory cue in video advertising.